Physical activity leisure time students from secondary school Ignacy Dzialynski in Golub-Dobrzyn - Kalinowska, Wioleta; Napierała, Marek; Gotowski, Rafał (Journal of Education, Health and Sport, 2017)
The aim of the study was to determine the degree of physical activity of students from the class of junior high schools in Golub-Dobrzyn. The study was performed by using a diagnostic survey research tool in the form of a survey of 90 middle school students from Golub-Dobrzyn. Conclusions: (1) The pupils are aware of what is physical activity for their health, why they take it, (2) Most of the lower secondary school students is not difficult physical activity, (3) Students recognized that physical activity is needed and it is good form dstresowania and perfect relaxation, (4) A healthy lifestyle is not a strange slogan for high school students.